Infantile perianal pyramidal protrusion with coexisting perineal and perianal hemangiomas: A fortuitous association or incomplete PELVIS syndrome? - Shyam B Verma; Uwe Wollina (Wolters Kluwer Medknow Publications, 2014)
Two cases of infantile perianal pyramidal protrusions (IPPP), one pyramidal in shape and one leaf shaped, are being described by us. Both were notable for coexisting hemangiomas in the close vicinity. To the best of our knowledge we are reporting these two variants of IPPP with the associated neighboring hemangiomas for the first time in Indian dermatologic literature. We suggest that this presentation may be a part of one of the syndromes that comprise anorectal malformations with hemangiomas like PELVIS syndrome and others mentioned in the table.